(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Poultry is an important source of protein and income for several households in Nigeria. However, the poultry industry is threatened by outbreaks of infectious diseases which may spread through the interaction of wild or migratory birds with poultry. The study aimed to detect and morphologically identify Eimeria species from faecal samples of chickens, pigeons and African fire finches collected from different poultry farms in Kaduna metropolis with a view to determining the role of migratory birds in the transmission of poultry coccidiosis. Two hundred and nine (209) faecal samples were freshly collected from 91 chickens, 61 pigeons, and 57 African fire finches and examined for the presence of Eimeria oocysts using Wisconsin faecal flotation technique; species identification was based on morphological characteristics of the sporulated oocyst. Eimeria oocyst were detected in all the sampling locations, seven species of Eimeria were identified namely E. tenella, E. brunetti, E. acervulina, E. necatrix, E. tropicalis, E. labbeana, and E. columbae. Eimeria brunetti was identified in both chickens and pigeons, while E. tenella, E. acervulina, and E. necatrix were identified in only chicken. On the other hand, E. tropicalis, E. labbeana, and E. columbae were found only in pigeons. The presence of Eimeria species in chickens, especially the acutely pathogenic E. tenella poses a significant challenge to poultry production. Furthermore, the infection among pigeons could serve as carriers of the protozoan from one farm to another. The results showed that African fire finches visiting poultry farms may not pose any threat in the transmission...